2022
DOI: 10.1186/s12887-022-03483-z
|View full text |Cite
|
Sign up to set email alerts
|

Reliability levels of motor competence in youth athletes

Abstract: This study aimed to analyze the reliability of the tests included in the motor competence assessment (MCA) battery and compare the effects of the number of trials per test. Thirty female volleyball players (14.6 ± 1.3 years of age) were tested. The participants performed two or three trials of each test. Intra-class correlation (ICC) was calculated, and a paired sample t-test analyzed the variations between trials (1st vs. 2nd vs. 3rd). Results revealed a significant difference between the first and the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Specifically, the ICC coefficients in this study are similar to those results reported by Sigmundsson et al [12], with a global ICC of 0.87 for their TMC battery; Rebelo-Gonçalves et al [16], who displayed reliability values of 0.79 and 0.72 on an eye-foot coordination test among young futsal players; or even Hoeboer et al [17], who reported ICC values that ranged from 0.80 to 0.88 on a motor skill competence test among 4-to 12-year-old children. Furthermore, the present results are similar to those reported by Silva et al [18], who found ICC values ranging between 0.72 and 0.99 on the six MCA tests in a sample of girls' volleyball youth players. However, it is important to note here that the latter only used one intra-session procedure (two or three attempts) and not between sessions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, the ICC coefficients in this study are similar to those results reported by Sigmundsson et al [12], with a global ICC of 0.87 for their TMC battery; Rebelo-Gonçalves et al [16], who displayed reliability values of 0.79 and 0.72 on an eye-foot coordination test among young futsal players; or even Hoeboer et al [17], who reported ICC values that ranged from 0.80 to 0.88 on a motor skill competence test among 4-to 12-year-old children. Furthermore, the present results are similar to those reported by Silva et al [18], who found ICC values ranging between 0.72 and 0.99 on the six MCA tests in a sample of girls' volleyball youth players. However, it is important to note here that the latter only used one intra-session procedure (two or three attempts) and not between sessions.…”
Section: Discussionsupporting
confidence: 92%
“…Hoeboer et al [ 17 ] considered the Athletic Skills Track (AST) among 4- to 12-year-old children and reported ICC values that ranged from 0.80 to 0.88, considering three age-bands assessed and a test–retest procedure with a two-week interval. Silva et al [ 18 ], with a sample of adolescent girl volleyball players, found ICC values that ranged from 0.72 to 0.99 on the MCA battery, although the test-retest procedure was only considered within a session with two or three trials and not between sessions. Finally, Smits-Engelsman et al [ 19 ] studied test–retest reliability of the Performance and Fitness (PERF-FIT) test battery with 72 children (33 boys and 39 girls, 5–12 years old), with an interval period between session one and two that varied from a minimum of one to a maximum of two weeks.…”
Section: Introductionmentioning
confidence: 99%
“…All test batteries for motor competence or motor development use sub-scales and total scores. In fact, the MCA has been used in recent years with each author using a composite of the tests to represent sub-scales and total MCA scores e.g., [ 16 , 17 , 18 ]. This practice has reflected the theoretical model assumed for MCA, long used in the field, that all tests and sub-scales have equal participation in the determination of the motor competence, but this had not been tested until now.…”
Section: Discussionmentioning
confidence: 99%
“…Although the MCA has been used with different populations and cultures [ 16 , 17 , 18 ], the method for scoring each of the three sub-scales (locomotor, stability, and manipulative) and for total MCA score, still needs to be defined. The initial theoretical framework on the development of motor skills [ 19 , 20 ] proposed an equal participation of the locomotor, stability, and manipulative components in overall motor competence.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability and validity data are also provided [ 27 ], showing perfect values (0.999 to 1.000) for all models, and all tests are quantitative (product-oriented) without a marked developmental ceiling effect. To ensure valid data collection and avoid the learning effect, three repetitions of each test were performed, with the first being characterized as familiarization and the subsequent two as the effective application of the test, as suggested by Silva et al [ 45 ]. Normative values based on sex and age can be assigned to each test, component, and MCA total score [ 26 ].…”
Section: Methodsmentioning
confidence: 99%